EFFECTIVENESS OF CLT BASED ON GAYONESE CULTURE IN ENHANCING JUNIOR HIGH STUDENTS' SPEAKING SKILLS IN CENTRAL ACEH - Abd Rahman (Program Studi Pendidikan Bahasa Inggris, 2024)
Most junior high schools do not give enough attention to designing and implementing communication between students and teachers. The Communicative Language Teaching (CLT) method aims to address the challenges faced in speaking activities and make students more interested in interacting with local culture-based texts. Every student should take the opportunity to communicate with their peers. This research is an experimental study conducted at SMPN 18 Aceh Tengah, focusing on eighth-grade students. The researcher employed quasi-experimental research, with the experimental group in class VIII A taught using CLT, while the control group in class VIII B was taught using conventional activities. Both classes took a pre-test at the beginning. Before the treatment, the two groups were balanced, starting from the same level. The post-test was administered at the end, after the treatment. The data collection instrument was a speaking test. The data were analyzed using t-test computation, and the collected data underwent descriptive and inferential statistical analysis. The research findings indicated a significant difference in the students’ speaking ability between the experimental group, who were taught using CLT, and those taught using conventional activities as demonstrated by the t-test. The t-observed value was higher than the t-table value (3.404 > 2.682 with df 48 at 10%). The probability value of 0.01 was lower than the significance level (0.01 < 0.05). In contrast, the control group showed a t-test result (1.393 < 2.682 with df 48 at 10%) and a probability value of 0.170, which was higher than the significance level (0.170 > 0.05). Based on the hypothesis analysis, the score of the experimental group was higher than that of the control group, leading to the conclusion that using CLT based on local culture (Budaya Gayonese) in language teaching effectively improves students’ speaking ability.